Outcomes after implementing the enhanced recovery after surgery protocol for patients undergoing tuberculous empyema operations - Xia, Zhaohua; Qiao, Kun; Wang, Haijiang; Ning, Xinzhong; He, Jianxing (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: Enhanced recovery after surgery (ERAS) protocols provide recommendations for care in various surgical fields. However, there is scarce information on the application of these protocols in tuberculous empyema surgery. The purpose of this research is to evaluate the outcomes of ERAS recommendations for patients who received tuberculous empyema surgery. Methods: A retrospective analysis was performed on patients who underwent tuberculous empyema surgery in our hospital from March 2011 to March 2016. The patients were divided into an ERAS group and a conventional control group. The main outcome measure was the postoperative median length of stay (including readmissions). Principles related to ERAS were documented, and the postoperative median hospital stay was analyzed statistically between the two groups. Results: A total of 92 patients underwent 93 consecutive tuberculous empyema surgical treatments. The postoperative fasting time, chest tube duration, and length of stay were shorter in the ERAS group compared with the control group. The volume of chest tube drainage in the ERAS group was significantly smaller than that of the control group. No statistical differences were observed in the postoperative complications and reasons for readmission between the two groups. Conclusions: Application of ERAS recommendations in patients receiving tuberculous empyema operations decreased the length of stay and chest tube drainage compared to the control group.